VD_FINDINFO Décision / 2012 / 621 vom 27. Januar 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 221 al. 2 CPP (CH), 222 CPP (CH)